Contesting colonial discourse: rewriting Murut history of resistance in British North Borneo from 1881 to 1915 - Fernandez, Callistus (Universiti Kebangsaan Malaysia, 1999)
This paper attempts to contest the colonial discourse on the history of Murut anti-British resistance. Anti-British resistance was part and parcel of reactions towards the British in the early periods of colonial rule from 1881-1915. In over three decades, the Muruts launched numerous rebellions against the British with disastrous defeats and heavy loss of lives. For the British, these actions were considered irrational, driven by the Muruts’ desire to return to their past ways of lawlessness and savage practices. To the Muruts, each rebellion marked a sign of resistance against the colonial encroachment into their social, economic, cultural and political life. Contrary to colonial views that downplay the significance of the Murut rebellions, the latter did forge a unified nation by 1915. The Rundum Rebellion of 1915 was the climax of Murut resistance. It contained features of a unified nation, a fixed geographical boundary, a leadership hierarchy, mobilization of labour and the control of violence to oust the British from Murut country. In essence, Murut resistance had a single goal – to gain independence from colonial rule.